Evaluation of Biological Value and Appraisal of Polyphenols and Glucosinolates from Organic Baby-Leaf Salads as Antioxidants and Antimicrobials against Important Human Pathogenic Bacteria - Maria J. Saavedra; Eduardo A. S. Rosa; Rosa Carvalho; Esperança Marques; Alfredo Aires (Molecules, 2013)
The present investigation has been carried out to investigate the biological role of four different types of baby-leaf salads and to study their potential as natural sources of antioxidants and antimicrobials against several isolates from important human pathogenic bacteria. Four single types of salads (green lettuce, red lettuce, rucola and watercress) and two mixtures [(1) red lettuce+green lettuce; (2) green lettuce + red lettuce + watercress + rucola] were assayed. The HPLC analysis revealed interesting levels of polyphenols and glucosinolates. The results showed a significant variation (p < 0.05) of polyphenols and glucosinolates with plant material. Nine different types of polyphenols grouped in three major classes were found: gallic acid, chlorogenic acid, caffeic acid and dicaffeoyltartaric acid (phenolic acids); quercitin-3-O-rutinoside, quercitin-3-O-rhamnoside, luteolin-7-O-glucoside and isorhamnetin (flavonoids); and cyanidin-3-glucoside (anthocyanins). Only three different glucosinolates were found: glucoraphanin; gluconasturtiin and 4-methoxy-glucobrassicin. A positive correlation was detected between polyphenol contents and antioxidant activity. Red lettuce and mixture 1 were the baby-leaf salads with the highest antioxidant potential. As for the antimicrobial activity, the results showed a selective effect of chemicals against Gram-positive and Gram-negative bacteria and Enterococcus faecalis and Staphylococcus aureus were the bacteria most affected by the phytochemicals. Based on the results achieved baby-leaf salads represent an important source of natural antioxidants and antimicrobial substances.